Focusing or fragmenting representation at work? : specialist trade union representation in the United Kingdom - Hodder, Andy; Lucio, Miguel Martínez (Emerald Publishing Limited, 2025)
Focusing or Fragmenting Representation at Work? reflects on how existing forms of workplace representation have changed in recent years and how new forms have developed. There is increasing interest in 'fine-tuning' representation, and in reflecting the complexity and nuances of specific groups of workers and themes at work such as equality, ecology, learning, and others. However, this study examines the extent of these developments and what they represent as innovative trade union roles. Chapters examine a wide range of highly prescient workplace issues, including: The changing role of the health and safety representative Equality representatives and new forms of trade union voice Learning, training and union representation Young workers in trade union revitalization 'Green reps' and the matter of ecological questions and politics Focusing or Fragmenting Representation at Work? ends by reviewing the challenges and debates on new forms of trade union representation and raises proactive and thought provoking questions for academic researchers examining trade unions, industrial relations and the sociology of work, as well as current trade unionists and trade union representatives. Featuring a balance of texts on the changing nature of and the history of trade union change and transformation, the series Trade Unionism gives space for in-depth, detailed analysis and captures key themes on the nature of internationalism and trade unionism.
Keywords: Labor unions -- Great Britain.; Business & Economics -- Labor -- Unions.; Trade unions.; Labour, income economics.; elektronické knihy; electronic books